BUAH CEMARA INTEGRASI DAN INTERKONEKSITAS SAINS DAN ILMU AGAMA - Arsyad, Azhar (Hunafa: Jurnal Studia Islamika, 2011)
Abstract:  Human beings possess three kinds of intruments to catch the whole reality. The three instruments are the five senses, reason and intellectuality as well as intuiion (revelation and inspiration)  whreas the Western intellectluas agree one instrument only, namely the five senses so that they  develope one research method only, namely observation method and  experiment. The observation method is continually developed  into very sopisticated level but it persistently derive from  the sense perception. Reason—in the form of reasoning—is employed, but only to choose, to decide and to perform reasoning, not as  other instruments to catch the reality. This makes the Western intellectuals different from the Muslim intellectuals since the later  admit the validity of not only the observation method  but also of the rational and intuitive method.  Kata Kunci: integrasi, interkonektisitas, sains,  ilmu agama, panca indera, akal